Antivirals Against Coronaviruses: Candidate Drugs for SARS-CoV-2 Treatment? - Santos, Igor de Andrade; Grosche, Victória Riquena; Bergamini, Fernando Rodrigues Goulart; Sabino-Silva, Robinson; Jardim, Ana Carolina Gomes (Frontiers in Microbiology, 2020)
Coronaviruses (CoVs) is a group of viruses from family Coronaviridae which can infect human and animals, causing mild to severe diseases. The ongoing pandemic of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) represents a global threat, urging into the development of new therapeutic strategies. Here we presented a selection of relevant compounds, from 2005 up to now, with in vitro and/or in vivo antiviral activities against human and/or animal CoVs. We also presented compounds that have reached clinical trials, as well as further discuss the potentiality of other molecules towards their application in (re)emergent CoVs outbreaks. Finally, through the rationalization of the data herein presented, we wish to encourage further research encompassing these compounds as potential SARS-CoV-2 drug candidates.